Use of soft, semi-soft and hard-seeded types of pomegranate (Punica granatunm) for improvement of fruit attributes - JALIKOP, S H; KUMAR, P SAMPATH (The Indian Journal of Agricultural Sciences, 2013)
Eighteen varieties or genotupes representisng soft;semi-hard seeded promgranate (Punica granatum L.)were evaluated for II fruit attributes, The result was studied for overall variation, variation within group and intergroupcomparison. The overall inter-genotypic differences were signiticant for fruit weight, rind thickness, total solu-ble solids (TSS), acidity, aril weight/fruit and aril weight/1OO g fruit. Signiticant variations were obselved within softtypes for 100-aril weight; within semi-soil varieties for 100-aril weight, TSS, seed mellowness and anil weight/100 gfruit; and within hard-seeded entries for rind thickness and aril weight 100 g truit. Comparison of soft, semi-'soft andhard-seeded types showed that for many fiuit attributes soft and semi-soil groups were similar whereas hard-seededwas a class apart, having signilicantly higher fruit weight and volume than the former 2 groups. But they possessed asmuch arils as soil and semi-soft seeded types with significantly low juice (%). The estimated juice/100 g fruit for hard,seededtypes was as low as 28 g in contrast to 44.5 g and 40.5 g for soft and semi-semi. seeded pomegranate respectively,Despite smaller fruit size, soft types therefore can he appropriate parents in evolving varieties for juice purpose,Hybridization within soil types was expected to generate restricted variability. as revealed by low CV for this group.The hard-seeded types could be good donor for improvement of some fruit attributes.